2016
DOI: 10.1590/0103-8478cr20160137
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between chronic inflammation, immunostaining and parasite load in the genital system of female dogs naturally infected with Leishmania infantum

Abstract: The aim of the present study was to investigate the correlations among chronic inflammatory reaction, immunostaining and parasite load in the genital system of female dogs naturally infected with Leishmania infantum . Animals (n = 10) used in this study were from the Department of Vector Control and Animal Surveillance of the municipality of Caruaru, state of Pernambuco, Brazil. Fragments of the vulva, vagina, cervix, uterine body, uterine horns and ovaries were submitted to histopathological analysis, immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…Previous studies involving dogs with parasitological confirmation of L . infantum have also reported a high frequency of positive results in the genital tract of males (94.7%) and females (90.0%) by IHC and qPCR [ 13 , 14 ]. In another study involving dogs with parasitological confirmation that originated from the same area as the animals of the present study, the frequencies of positive results in the genital tract were 90% among males and 80% among females [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies involving dogs with parasitological confirmation of L . infantum have also reported a high frequency of positive results in the genital tract of males (94.7%) and females (90.0%) by IHC and qPCR [ 13 , 14 ]. In another study involving dogs with parasitological confirmation that originated from the same area as the animals of the present study, the frequencies of positive results in the genital tract were 90% among males and 80% among females [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors [ 13 ] observed a lower frequency of positive results in the prostate (78.9%), but higher than that found in the present study. In bitches, studies found a higher frequency of positive results in the uterus (80%), followed by the vagina (70%) and vulva (60%) [ 14 ]. These results differ from the present study in which the frequencies of positive results were much higher in the vulva and vagina compared to the uterus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations